Thoughts on the construction of public health informatization for community health archives grass roots management system - Wang, Yong; Zhu, Chaonan (Frontiers in Public Health, 2023)
In recent years, high-quality and efficient medical services have become an urgent need of people under economic growth. With the growth of social economy and the continuous improvement of people’s living standards, people expect to receive high-level medical services, and the requirements for medical care are also getting higher and higher. Although considerable progress has been made in deepening medical reform, the medical security system has been continuously improved. However, the problems of rising medical costs, lack of access to medical services, uneven distribution of medical resources, low efficiency of medical services, and uneven medical quality still exist objectively. This paper first analyzed the significance of public hygiene informatization construction and highlighted the elements of public health informatization construction. It also described the current situation of health information construction and the existing problems of community health information. Then, this paper expounded the construction of public health information based on the community health archives grass-roots management system, and discussed the construction of a health information platform with community residents’ health archives as the core. The importance of the construction elements of the health information platform based on community health records was found, and the functions of the health information platform based on community health records were discussed. After that, the functions of the community medical information archives management system were proposed and studied from three aspects: the composition of the community medical information archives management system, the management and problems of the community medical information archives management system, and the development requirements of the community medical information archives management system. The algorithm based on decision tree model was proposed to enhance public health informatics. Finally, based on experiments and surveys, Internet technology and decision tree model algorithm were introduced into the construction of the public health information system of the community health archive system to build a new public health information system, which can improve the satisfaction by 23%.